Etiket Persidangan dan Integritas Advokat: Relevansi Kasus Firdaus Oiwobo dalam Penegakan Hukum yang Bermartabat - Moza Hadi Maheswara Kunto Jayamahe (CV. ITTC INDONESIA, 2026)
The dignity of law enforcement depends on advocates’ integrity and adherence to courtroom etiquette. This study examines ethical violations in the courtroom through a case study of advocate Firdaus Oiwobo’s conduct and legal record. Employing normative legal analysis and empirical review of documents, media coverage, and bar association decisions, the research evaluates the compatibility of the subject’s behavior with the Indonesian Advocates’ Code of Ethics (KEAI) and indicators of contempt of court. Findings reveal tensions between vigorous client representation and ethical limits: certain public statements and in-court conduct risk undermining the judiciary’s dignity and eroding public trust. The study also assesses bar organizations’ roles in disciplining members, highlighting issues such as multiple bar bodies, digital-era challenges, and inconsistent sanctioning. Policy recommendations include strengthening transparent internal oversight, harmonizing ethical standards across associations, continuous ethics education, and coordination with judicial institutions to clarify contempt boundaries. The results aim to inform policy measures to strengthen advocates’ integrity and uphold the judiciary’s authority in Indonesia.